On the Measurement of the Rate of Intramolecular Vibrational Energy Redistribution via High Resolution Molecular Beam Optothermal Spectroscopy. Issue 3 (1991) - Lehmann, Kevin K.; Pate, Brooks H.; Scoles, G.
Abstract : Using frequency resolved techniques we have been able to measure the rate of intramolecular vibrational energy redistribution in a number of substituted acetylenes. The method of IVR rate determination is discussed with respect to time domain measurements. The lifetimes we have determined have been quite long, ranging from a few hundred ps to a few ns. Interesting behavior of the rate as a function of the structure of the molecule has been observed. Results show sensitivity of the IVR rate to heavy mass substitution and the possibility of chromophore determined lifetimes.